The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2009
DOI: 10.1073/pnas.0809100106
|View full text |Cite
|
Sign up to set email alerts
|

An oxygen-sensitive mechanism in regulation of epithelial sodium channel

Abstract: Epithelial sodium channels (ENaCs) are of immense importance, controlling Na ؉ transport across epithelia and thus playing a central role in all aspects of fluid clearance as well as numerous other functions. Regulation of these channels is critical. Here, we show that haem, a regulator of Na ؉ transport, directly influences ENaC activity, decreasing channel-open probability (but not unitary conductance) in inside-out patches (but not outside-out). Conversely, exposure to the protein in the presence of NADPH a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
48
3
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(57 citation statements)
references
References 48 publications
4
48
3
2
Order By: Relevance
“…In the case of ion channel regulation, it has recently emerged that there is a role for heme (12,(23)(24)(25)(26), but the observations are largely empirical, so that the molecular basis for the regulatory control within individual channel proteins has yet to be properly defined. A number of heme-responsive motifs (27) have been suggested to be involved: these include Cys/Pro (CP) motifs using thiolate ligation to the heme as in the P450s or Cys/His motifs (3,14).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of ion channel regulation, it has recently emerged that there is a role for heme (12,(23)(24)(25)(26), but the observations are largely empirical, so that the molecular basis for the regulatory control within individual channel proteins has yet to be properly defined. A number of heme-responsive motifs (27) have been suggested to be involved: these include Cys/Pro (CP) motifs using thiolate ligation to the heme as in the P450s or Cys/His motifs (3,14).…”
Section: Discussionmentioning
confidence: 99%
“…There is as yet no evidence that ion channels proteins use similarly specialized biosynthetic machinery; thus, it seems unlikely that their heme is covalently attached. Neither the epithelial sodium channels (24) nor the A-type K + channels (23) contain a CXXCH motif, which we interpret to mean that the mode of heme binding is most likely not the same across all ion channels.…”
Section: Discussionmentioning
confidence: 99%
“…In many heme proteins including soluble guanylyl cyclase, heme is bound or coordinated in part by an amino acid sequence typically containing a histidine or cysteine residue, which acts as an axial fifth ligand (in addition to the four bonds provided by the nitrogen atoms of the protoporphyrin-IX ring to the iron center) to the redox-sensitive iron center, and water or a bound gas molecule acts as the sixth ligand (15). However, recent advances revealed a novel role of heme as a nongenomic modulator of ion channel functions, first exemplified for the largeconductance voltage-and Ca 2+ -dependent K + channel (Slo1 BK) (16) and later for the epithelial Na + channel (17). Detailed analysis of the biophysical action of heme [ferrous iron (Fe 2+ )] or hemin [ferric iron (Fe 3+ )] on the Slo1 BK channel demonstrated that hemin is a potent modulator of the allosteric gating mechanism of the channel (18), and mutagenesis studies have indicated the sequence CKACH located in the cytoplasmic C terminus of the channel plays a critical role (16,19).…”
Section: N-type Inactivationmentioning
confidence: 99%
“…Using immunofluorescence, we found that HO-1 robustly stimulates cytotrophoblast ␤-ENaC protein expression. While there is limited evidence in the literature related to the role of HO-1 in regulating ␤-ENaC expression, a recent study by Wang et al (28) found that heme (the substrate for HO) inhibits, while carbon monoxide (HO metabolite) stimulates, ENaC activity in renal epithelial cells. However, another study demonstrated that CO has the capacity to inhibit amiloride-sensitive channels in airway epithelial cells (3).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, pharmacological inhibition of HO-1 promotes hypertension and reactive oxygen species in pregnant rats (12). Interestingly, heme, the substrate of HO-1, and CO, a HO-1 metabolite, are powerful inducers of ENaC activity in renal epithelial cells (28). However, whether the beneficial effects of HO-1 induction in placental ischemia are mediated by ␤-ENaC is unknown.…”
mentioning
confidence: 99%